2018
DOI: 10.12691/jfnr-6-7-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Modifications of Nitrogen Intake Decreases Inflammation and Promotes Rejuvenation of Spleen in Aged Mice

Abstract: The spleen is a lymphoid organ with multiple functions including blood filtration and immune activity.Aging changes the spleen's anatomy for both immune and stromal cells and can lead to immunesenescence, contributing to the increased rates of mortality and morbidity commonly observed in the elderly. Much evidence indicates that the combination of food quantity and quality can influence chronic inflammatory states in the spleen. Quantitative amino-acids (AA) adequacy is pivotal to maintain cell integrity in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 85 publications
2
5
0
Order By: Relevance
“…We also observed that the EAA-100% diet reduced Hpg level, but not NLR ratio, more than StD. This confirms that EAA have anti-inflammatory activity as observed previously [11,40].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also observed that the EAA-100% diet reduced Hpg level, but not NLR ratio, more than StD. This confirms that EAA have anti-inflammatory activity as observed previously [11,40].…”
Section: Discussionsupporting
confidence: 91%
“…We also observed that the EAA-100% diet reduced inflammation, as suggested by the lower Hpg level found in animals on this diet, even when compared to StD. This is in agreement with the anti-inflammatory activity of EAA observed in previous experimental [11,40] and clinical settings [1,54,55]. Those effects on inflammation modulation could represent one of the mechanisms underpinning the longer lifespan reached by these animals.…”
Section: Discussionsupporting
confidence: 91%
“…A possible limitation of this study is the exclusive application of IHC to support our results. However, as applied in a previous spleen study [ 2 , 87 ], this choice was dictated by the fact that the gut also contains heterogeneous cell population (enterocytes, goblet cells, Paneth’s cells, myocytes, etc.). Consequently, histopathological changes and especially the exact location of markers is possible alone with IHC and HC.…”
Section: Discussionmentioning
confidence: 99%
“…The other AAs can be synthesized in an autonomous way by the body, and therefore are defined non-essential (NEAAs). To best survive, all organisms must maintain a full complement of the AAs, best if with excess of EAAs [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, we should note that no dietary proteins have an EAA/NEAA ratio > 0.9, whereas, conversely most proteins have a <0.7 ratio at best. Interestingly, experimental data show that special EAA mixtures with an EAA/NEAA ratio >1 increases lifespan (23) and albumin (24), and also reduces inflammation in healthy mice (25,26). This would suggest that NEAA are not indispensable for cell life and that they are synthesized according to metabolic needs if adequate amounts of EAA are provided.…”
Section: Nutritional Supplementationmentioning
confidence: 99%